Nilai-nilai Keimanan dalam Pemikiran Sejarah Ibnu Khaldun pada Kitab al-Muqaddimah - Sidik, Saepul Japar; Tamam, Abas Mansur; Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2021)
Ibn Khaldun's Kitab al-Muqaddimah is known as a monumental historical work. From his introductory work on his book al-'Ibarnya, Ibn Khaldun is known as the Father of Historiography and the Historian of Philosophy. His theories about history are often known as empirical-rationalist works. However, works that are considered empirical-rationalist do not pay attention to the values of faith in them. Even other researchers say that Ibn Khaldun's historical thoughts were reconstructed from the values of revelation (al-Qur'an and al-Hadith). The research method used is the library method or also known as libraly research. The temporary conclusion from this research is that there are values of faith in the historical thought of Ibn Khaldun in his al-Muqaddimah book. Abstrak Kitab al-Muqaddimah karya Ibnu Khaldun dikenal sebagai karya sejarah yang monumental. Dari karya pengantar atas kitab al-‘Ibarnya inilah Ibnu Khaldun dikenal sebagai Bapak Historiografi dan Sejarawan Filosof. Teori-teorinya tentang sejarah, acapkali dikenal sebagai karya yang empiris-rasionalis. Namun demikian, karya yang dinilai empiris-rasionalis tidak mengindahkan nilai-nilai keimanan di dalamnya. Bahkan peneliti lain menyebutkan bahwa pemikiran sejarah Ibnu Khaldun direkonstruksi dari nilai-nilai wahyu (al-Qur'an dan al-Hadits). Metode penelitan yang digunakan adalah metode pustaka atau disebut juga dengan libraly research. Konklusi sementara dari penelitian ini adalah terdapat nilai-nilai keimanan dalam pemikiran sejarah Ibnu Khaldun pada kitab al-Muqaddimahnya.